Wine, Spirits and the Lung: Good, Bad or Indifferent? - Kamholz, Stephan L (American Clinical and Climatological Association, 2006)
The putative cardiovascular risks and benefits of the ingestion of wine and alcohol-containing spirits have been well publicized; however, less attention has been focused upon the health effects of wine and spirits consumption on the respiratory system. This paper will highlight epidemiologic, clinical and experimental data on the effects of wine and distilled spirits [and the chemical components thereof] on lung function, chronic obstructive pulmonary disease progression, lung cancer risk, risk of developing acute respiratory distress syndrome, high altitude pulmonary edema and wine [sulfite] associated asthma. Several studies have demonstrated a positive [beneficial] effect of light-to-moderate wine consumption on pulmonary function, while chronic ingestion of distilled spirits may have either no effect, or a negative effect. Studies in Scandinavia, Europe and South America have suggested a possible protective effect of wine ingestion against lung cancer, especially adenocarcinoma. Resveratrol [3,5,4′-trihydroxystilbene] a polyphenolic compound found in red wine, has anti-oxidant, anti-inflammatory and estrogen agonist effects and may be responsible for some of the health benefits of wine. The spectrum of potentially beneficial clinical effects of resveratrol and other wine-derived compounds is discussed.